Diseño e implementación de cableado estructurado bajo la norma tia-eia-568a-b, en el laboratorio de redes y mantenimiento de la Universidad Técnica de Cotopaxi extensión La Maná en el año 2014 - Chalco Toro, Alexis Javier (2015)
Communications have evolved over time, thus being structured cabling system today a fundamental part when designing a data network. The implementation of a structured cabling system under the EIA / TIA / 568A-B standard in the Laboratory of Networking and Maintenance of the Technical University of Cotopaxi, is based on several aspects to comply, with the improvement of the network services more relevant. Research methodology, this research is based on a series of processes and methods for performing a particular purpose, through field research, bibliographic and documentary research representative could know the characteristics of structured cabling system, and the use of research methods, such as inductive, analytical scientist who start from a known reality....